Impact of Displacement on Women and Female-Headed Households: A Mixed Method Analysis With a Microeconomic Touch - Amirthalingam, Kopalapillai; Lakshman, R.W.D. (Journal of Refugee Studies, Oxford University Press, 2012)
This article analyses forced displacement through a gender lens, focusing on the experiences of women and also of female headed households. It uses a set of qualitative as well as quantitative data, covering internally displaced persons (IDPs) in Sampur, Sri Lanka. The study revealed that women have particular protection and assistance needs that exceed the needs of men. In addition, the coping mechanisms used by displaced women were sometimes found to be more effective than those used by men. Moreover, there are economically significant differences between the ways female and male headships pool resources to cope with displacement. The fieldwork was carried out in August 2007 and in April 2008, at welfare centres in Batticaloa which received the IDPs from Sampur in 2006. This group remains displaced at the time of writing.
Keywords: Sri Lanka; Internally Displaced Persons (IDPs); Gender; Conflict Induced Displacement (CID); Coping strategies; Female headship